Intratympanic steroid injection for sudden sensorineural hearing loss in a patient on hemodialysis. Issue 1 (18th June 2013) - Wu, Rui‐Xin; Chen, Chun‐Chi; Wang, Chih‐Hung; Chen, Hsin‐Chien
Abstract Sudden sensorineural hearing loss (SSNHL) is being described with increasing incidence among patients with end‐stage renal disease (ESRD) undergoing hemodialysis (HD). There are no widely accepted guidelines in the medical literature for the appropriate management of this medical emergency. Administration of systemic steroids remains the mainstay of the management of SSNHL in conjunction with the supportive treatment, in this vulnerable group of patients, as well. However, encouraged by the evolving evidence on the efficacy of the intratympanic steroid injections (ITSI) in the treatment of SSNHL among patients without renal disease—we successfully treated SSNHL in an elderly diabetic with sepsis due to bilateral pneumonitis undergoing regular HD treatment with multiple ITSI and antibiotics resulting in complete recovery of hearing function within 3 months of onset of the first symptoms.